Arthropod Parasites of Rodents in Khorram Abbad district, Lorestan Provincen of Iran - A Shayan; J Rafinejad (Tehran University of Medical Sciences, 2006)
Ectoparasites are considered as the main vectors of zoonotic diseases. They play an important role for transmission of wide variety of diseases such as CCHF, leishmaniosis and plague to human and vertebrates. Mammals, especially rodents, are the most important reservoirs of zoonotic diseases. The aim of this study was to identify the ectoparasites of rodents captured in Korram-Abad, Lurestan Province, Iran during year 2002-2003. Rodents were live trapped from 24 localities in six major land-resource areas. A total of 167 alive rodent specimens were transported to the laboratory and after anesthetizing by chloroform their ectoparasites were removed. Collected ectoparasites were mounted and identified. Altogether 218 ectoparasites related to 3 orders, 6 families, 6 genera, and 7 species were systematically recognized. Fleas with 3 species had the most number of species, mites and lice allocated the most (64.67%) and the least (3.21%) frequency of ectoparasites, respectively. Ectoparasites were more prevalent in Zagheh area (38.99%). Haemolaelaps glasgowi (42.2%) was the most common ectoparasite while, Nosopsyllus irranus only constituted approximately 0.91% of specimens. Zagheh area could be a high-risk zone for zoonotic disease transmission due to poor hygienic circumstances